2009
DOI: 10.1007/400_2009_32
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Precursor Processing

Abstract: The singular gene for a peptide hormone is expressed not only in a specific endocrine cell type but also in other endocrine cells as well as in entirely different cells such as neurons, adipocytes, myocytes, immune cells, and cells of the sex-glands. The cellular expression pattern for each gene varies with development, time and species. Endocrine regulation is, however, based on the release of a given hormone from an endocrine cell to the general circulation from whose cappilaries the hormone reaches the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 107 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…These bioactive peptides with short sequences are used as biomaterials for tissue engineering, regenerative medicine, and peptide hormones, even with anticancer activity. [2][3][4][5] It has been reported that bioactive peptides play a very important role in the regulation of physiological functions such as oxidative stress, hypertension, thrombosis, cancer, bacterial infections, inammation, diabetes, obesity, hypercholesterolemia, immunoregulation, binding of minerals and opioid activities. 6 Bioactive peptides can be obtained from animal, plant and microbial proteins.…”
Section: Introductionmentioning
confidence: 99%
“…These bioactive peptides with short sequences are used as biomaterials for tissue engineering, regenerative medicine, and peptide hormones, even with anticancer activity. [2][3][4][5] It has been reported that bioactive peptides play a very important role in the regulation of physiological functions such as oxidative stress, hypertension, thrombosis, cancer, bacterial infections, inammation, diabetes, obesity, hypercholesterolemia, immunoregulation, binding of minerals and opioid activities. 6 Bioactive peptides can be obtained from animal, plant and microbial proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention in modern biology and medicine is paid to studying the involvement of peptidic nature's substances in regulating the hemostasis of some cell populations and their role as signaling molecules providing communicative links in normal and pathological conditions (1,2). Such studies include various works on the primary participants in the blood coagulation system and their functioning (3), mechanisms of platelet activation (4), as well as the interaction between them (5) and active agents during thrombosis and thrombo-inflammation (6).…”
Section: Introductionmentioning
confidence: 99%